مہارتوں کا نظم:انبیاء علیھم السلام اور خیر القرون کی روشنی میں تحقیقی مطالعہ: System of Skills: An Analytical Study in the Light of the Prophets (ʿAlayhim al-Salām) and the Best Generations (Khayr al-Qurūn) - Amna Waqar; Dr. Saima Farooq (jihat-ul-islam, 2024)
Allah created human beings in the best form (ahsani taqweem), endowed them with countless abilities, and made them responsible for using those abilities in the best possible way. Islam, in accordance with human nature, temperament, and disposition, encouraged the acquisition of skills and motivated their development. For example, the Prophet ﷺ never encouraged Khalid ibn al-Walid رضي الله عنه to compose poetry; rather, he praised his excellent swordsmanship, acknowledged his mastery of that art, and granted him the honorable title of “Saifullah” (the Sword of Allah). Islam is the religion of nature (Deen al-Fitrah), and progress in every beneficial aspect of life is the right of a Muslim. Thus, it is natural — and, in the light of Islamic teachings, a commendable act — for a Muslim to attain excellence in various skills. For example, engaging in business requires certain abilities that lead to success, and success is only possible when one is aware of the knowledge and methods necessary for the development of those skills. Similarly, in the case of leadership, Islam has emphasized the qualities required and directed attention toward attaining those qualities in the best possible manner.